Pengaruh Kompetensi dan Motivasi Terhadap Kualitas Laporan Keuangan Satuan Kerja Perangkat Daerah - Pratiwi, Feren Ayu; Nurhasanah, Nunung; Suartini, Sri (Universitas Gorontalo, 2024)
The aim of this research is to ascertain how competence and motivation within the Karawang Regency Government influence the quality of SKPD financial reports. In this study, a sample of sixty respondents was used for sampling. By using a questionnaire instrument, a survey approach was used in the data collection procedure. Validity test, reliability test, normality test, descriptive analysis, and verification analysis using multiple linear regression were used to analyze the data. Using SPSS version 27 software for data processing. Research findings show that, apart from statistical testing, motivation and competency variables have a major impact on the quality of financial reports. In addition, the quality of financial reports is significantly influenced by motivation and competency variables, at different levels.